2021
DOI: 10.1155/2021/9523836
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in the Hospitalized Elderly in Tanzania: Prevalence, Severity, and Micronutrient Deficiency Status

Abstract: Introduction. Anaemia is a common problem in sub-Saharan Africa. While most literature has focused on children, women of childbearing age, and pregnant women, data for the elderly population are relatively scarce. Anaemia exhorts negative consequences to functional ability of elderly patients, both physically and cognitively. The purpose of this study was to determine the prevalence of anaemia, severity, and micronutrient deficiency status in the elderly hospitalized patients in Tanzania. Methods. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
6
2
Order By: Relevance
“…Furthermore, our study anemia prevalence was lower than, reports of studies done in Tanzania (79.5%) by Chamba et al, 50 France (53%) by Petrosyan et al, 51 India (68.7%) by Pathania et al, 52 Turkey (54.9%) by Sahin et al, 53 and Ethiopia (54.5%) by Melku et al 26 The difference might be due to comorbidity of disease and difference in the study subjects, since the elderly of this study who sought medical intervention in the outpatient department, as opposed to the study subjects in the other studies were institutionalized in longterm care facilities, and the study subjects, and the use of different study design than the current study. Our findings were also lower than those reported by Dunn et al 54 77% Mary Potter Hospices in New Zealand.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, our study anemia prevalence was lower than, reports of studies done in Tanzania (79.5%) by Chamba et al, 50 France (53%) by Petrosyan et al, 51 India (68.7%) by Pathania et al, 52 Turkey (54.9%) by Sahin et al, 53 and Ethiopia (54.5%) by Melku et al 26 The difference might be due to comorbidity of disease and difference in the study subjects, since the elderly of this study who sought medical intervention in the outpatient department, as opposed to the study subjects in the other studies were institutionalized in longterm care facilities, and the study subjects, and the use of different study design than the current study. Our findings were also lower than those reported by Dunn et al 54 77% Mary Potter Hospices in New Zealand.…”
Section: Discussioncontrasting
confidence: 73%
“…This study was concordant with the studies conducted in Germany 60%, 28 Benin 61.8%, 4 and Uganda 64.3%. 5 However, Results from the present study revealed a lower prevalence of anemia than the previous studies conducted in Pakistan 71%, 3 Bahrain 72.2%, 2 and Tanzania 79.5%, 11 and a higher prevalence than other similar studies done in Italy 48%, 6 Germany 54.2%, 29 Pakistan 55.5%, 30 and Tanzania 44%. 12 This inconsistency Normocytic normochromic (33.2%) blood picture was the most common morphological type of anemia, followed by microcytic hypochromic (27.9%) anemia.…”
Section: Discussioncontrasting
confidence: 66%
“…A Structured questionnaire was prepared from different literature. 3,4,11,21,22 A total of nine data collectors (one senior clinical nurse, one senior medical resident, and one senior medical laboratory professional) from each of the selected hospitals collected socio-demographic characteristics, lifestyle, and history and clinical conditions (age at admission, cause of hospital admission, and laboratory tests) of each patient's data. The study participants' weight and height were measured using a digital weight scale with a connected height scale (Adult Scale ASTOR).…”
Section: Data Collection and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of anaemia in geriatric patients: a retrospective hospital-based study from Northern Sri Lanka Majority had a moderate severity(56.6%), followed by severe anaemia (28.8%) in our study. A hospital-based study done in Tanzania revealed that more than two-third of the participants were having either moderate or severe anaemia (27). However, there were contrasting results in other studies where mild anaemia was mainly identified in the older adult population (2,5).…”
Section: Research Lettermentioning
confidence: 97%